Product competition and R&D investment under spillovers within full or partial collusion games - Kai Zhao (Latin American Economic Review, 2015)
The paper investigates firms' behavior and outcomes (levels of cost-reducing R&D, output, profit and welfare in equilibrium) in a differentiated duopoly with process innovation. One of the important features in this paper is that spillovers operate in the R&D stage and are tied to the degree of product substitutability as well as the extent of technological proximity/alienation of the research paths leading to cost reduction. Using this feature, the paper tries to explore and compare four separate organization setups (Full Competition, Semi-collusion in Production, Semi-collusion in R&D and Full Collusion). It is found that under technological proximity, competitions at the upstream stage depress R&D investment, and firms colluding in R&D regardless of their production strategy always yield more profit and generate higher social welfare than firms colluding in output; under technological alienation, R&D cooperation may reduce firms' interest to invest in R&D, and it is possible that firms in the Full Collusion regime produce most and generate the highest level of social welfare.
Keywords: D43; L13; O31; 330; R&D; Spillover; Semi-collusion; Product differentiation; Horizontal merger